Effect of grape wine-making by-product extract addition on the quality of dry white wine during storage period - WANG Yong, ZHU Zheng, LI Zhuoyu, YU Ran (Zhongguo niangzao, 2024)
Extracts from grape wine by-products (grape seeds and grape vine stems) were added to dry white wine to investigate the changes of color parameters, redox potential, antioxidant capacity and phenolic compounds of dry white wine during storage for 12 months. Sensory evaluation was carried out to evaluate the effects of different grape wine-making by-product extracts addition on the quality of dry white wine during storage. The results showed that the dry white wine with 300 mg/L grape vine stem extract had the highest L* value and the lowest b* value; the redox potential was 222 mV, which increased by 6% compared to the wine sample with grape seed extract addition, but decreased by 21% compared to the blank control group; the free radical scavenging rates of 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis (3-ethylbenzothiazoline -6- sulfonic acid (ABTS) were 41.24% and 58.92%, respectively, which were 9.73% and 13.66% higher than those of the blank control group; the content of total phenols, catechins, epicatechins were 1 018.7 mg/L, 32.60 mg/L, and 18.76 mg/L, respectively, which decreased compared to the wine sample with grape seed extract addition, but increased by 37.24%, 100.74%, and 68.71% compared to the blank control group; the sensory score was the highest of 82 points. In summary, adding 300 mg/L grape vine stem extract had a good protective effect on the quality of dry white wine during storage.